A logistic model study of endogenous and exogenous factors affecting polish SMEs’ internationalization speed - Nowiński, Witold; Bakinowska, Ewa (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
This study is focused on the issue of early internationalization. Its key research objective was to assess how endogenous and exogenous factors discussed in prior research on SME internationalization affect the speed of internationalization. The study is based on data collected via survey research conducted among small and medium private Polish exporters. The results from the survey research are analyzed with the use of non-parametric statistical methods and logistic regression analysis. Our findings indicate that SMEs are pushed to follow the early internationalization path mainly by internal capabilities related to international social capital, to a smaller extent by their unique resources or capabilities, and indirectly by prior international business experience of their managers. Simultaneously they are pulled by opportunities stemming from the possibility to achieve higher margins from foreign sales
Argumenta Oeconomica, 2012, Nr 1 (28), s. 155-180
Keywords: internationalization; SMEs; Central and Eastern Europe; entrepreneurship